PENGARUH ZAKAT, PENDAPATAN ASLI DAERAH, ANGKATAN KERJA, DAN PENANAMANAN MODAL TERHADAP PERTUMBUHAN EKONOMI JAWA TENGAH - Kurniawati, Erlina; Irkhami, Nafis (Program Studi Ekonomi Pembangunan, 2024)
The research aims to analyze the influence of zakat, local income, labor force, and investment both domestic and foreign on economic growth in Central Java. The data used is secondary from the Central Statistics Agency and BAZNAS in 10 districts/cities in Central Java Province during the 2018-2022 periods. The data used comes from. The method used is panel data regression analysis. The research results show that the variables of domestic investment and labor force do not have a significant effect on economic growth. Variables that have a significant influence on economic growth in Central Java are zakat, local income and foreign investment.